The cerebellar "tilted telephone receiver sign" enables prenatal diagnosis of PHACES syndrome. (November 2018) - Leibovitz, Zvi; Guibaud, Laurent; Garel, Catherine; Massoud, Mona; Karl, Katrin; Malinger, Gustavo; Haratz, Karina K.; Gindes, Liat; Tamarkin, Mordechai; Ben-Sira, Liat; Lev, Dorit; Shalev, Josef; et al.
Abstract: Objectives: To describe a unique posterior fossa neuroimaging characteristic of prenatal PHACES syndrome (PS): unilateral cerebellar hypoplasia (UCH) and ipsilateral posterior fossa (PF) cyst communicating with an asymmetrically distended 4th ventricle. Methods: The registries of seven prenatal diagnosis centers were searched for cases with PF findings and a postnatal diagnosis of PS. All records were evaluated for ultrasound and MRI findings and the postnatal outcome. PS was diagnosed after birth according to the consensus statement on diagnostic criteria for PS from 2009. The imaging findings of the PS fetuses were compared to a group of consecutive cases with fetal UCH, whose postnatal diagnosis was not PS. Results: The PS group included 10 fetuses. All were referred due to UCH accompanied by an ipsilateral retrocerebellar cyst. All pregnancies resulted in livebirths, all newborns had a large segmental facial hemangioma. In all PS fetuses the affected cerebellar hemisphere was upwardly displaced by an ipsilateral PF cyst communicating with an asymmetrically distended 4th ventricle. An upwardly rotated and deviated vermis merged with the contralateral cerebellar peduncles forming an elongated oblique connection between the cerebellar hemispheres, resulting in a unique cerebellar shape, "a tilted telephone receiver sign" (TTRS), on the coronal plane through the upper vermis.The non-PS group included 11 fetuses with UCH: clastic cerebellar lesions (8) and a unilateral PF arachnoid cyst (3). The TTRS was not depicted in any of them (p < 0.0005). Conclusions: The cerebellar TTRS is a specific fetal imaging feature of PHACES syndrome enabling its prenatal diagnosis. Highlights: The postnatal diagnostic criteria for PHACES syndrome have been published in 2009. There are no diagnostic criteria of PHACES syndrome in utero. The cerebellar "tilted telephone receiver" sign can be considered a prenatal diagnostic criterion of fetal PHACES syndrome.